2018
DOI: 10.1021/acs.energyfuels.7b03161
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxy-fuel Combustion on Ash Properties and Sintering Strength Development

Abstract: For a successful implementation of the oxy-fuel combustion technology, a good understanding of ash-related issues has to be achieved. Knowledge is still lacking on how oxy-fuel combustion can affect ash properties and its sintering behavior. These are the focus of the present work. Combustion experiments of a sub-bituminous coal were carried out in a drop-tube furnace at 1573 K and under air and different oxy-fuel conditions (i.e., OXY21, 21 vol % O2/79 vol % CO2; OXY27, 27 vol % O2/73 vol % CO2; and OXY32, 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…They found that the ash deposition under oxyfuel combustion was basically similar to air combustion based on the SEM images of the deposits, the deposit chemistry and the visual observations of the deposit build-up. The discrepancies in the effect of oxyfuel combustion on the ash deposit formation can be found in these experimental findings and it can be concluded that: (i) the effects mainly result from the aerodynamic changes in the small scale furnaces, rather than the chemical changes in the fly ash/deposit [6][7][8][9]; (ii) the effect of the oxyfuel combustion condition on the fly ash formation could be decreased when the flame temperature/char temperature are close to those in the air combustion [12]. Therefore, it is important to undertake a CFD analysis on the effect of the aerodynamics on the ash deposition in order to understand the detailed effect of oxyfuel combustion on the particle impaction and sticking behaviours.…”
Section: Introductionmentioning
confidence: 76%
“…They found that the ash deposition under oxyfuel combustion was basically similar to air combustion based on the SEM images of the deposits, the deposit chemistry and the visual observations of the deposit build-up. The discrepancies in the effect of oxyfuel combustion on the ash deposit formation can be found in these experimental findings and it can be concluded that: (i) the effects mainly result from the aerodynamic changes in the small scale furnaces, rather than the chemical changes in the fly ash/deposit [6][7][8][9]; (ii) the effect of the oxyfuel combustion condition on the fly ash formation could be decreased when the flame temperature/char temperature are close to those in the air combustion [12]. Therefore, it is important to undertake a CFD analysis on the effect of the aerodynamics on the ash deposition in order to understand the detailed effect of oxyfuel combustion on the particle impaction and sticking behaviours.…”
Section: Introductionmentioning
confidence: 76%
“…That observation shows that the breaking stress is very sensitive at the beginning stage of the ash sintering process. In turn, the study of the initial stage of the ash sintering process is very important in identifying the mechanisms of transformation of the mineral substance of solid fuels during combustion under different conditions [22,30].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al () employ an optically accessible flat-flame burner to reveal the effect of CO 2 and H 2 O on the formation of incipient ultrafine particulate matter (PM) from the combustion of a high-sodium lignite under oxy-fuel conditions. Wu et al () study the impacts of oxy-fuel conditions on ash properties and sintering behavior from the combustion of a pulverized sub-bituminous coal at 1300 °C in a drop-tube furnace. Chen et al () simulate the vaporization of inorganic matter from the combustion of a single coal char particle under oxy-fuel conditions.…”
Section: Topic Reviewmentioning
confidence: 99%
“…Wu et al(10.1021/acs. energyfuels.7b03161)29 study the impacts of oxy-fuel conditions on ash properties and sintering behavior from the combustion of a pulverized sub-bituminous coal at 1300 °C in a drop-tube furnace. Chen et al (10.1021/acs.energyfuels.…”
mentioning
confidence: 99%